The Challenge of Governing Africa's New Agricultural Investment Landscapes: An Analysis of Policy Arrangements and Sustainability Outcomes in Ethiopia and Nigeria - Schoneveld, George C. (MDPI, 2015)
In the context of globalization, market liberalization, and deregulation, many African governments are embracing the potential of private agricultural investment to address structural issues within their agricultural economies. Sustainably integrating these investments into target landscapes, however, poses a number of governance challenges since it requires careful reconciliation of competing needs, priorities, and land uses. This paper examines the effectiveness of existing policy arrangements in managing these conflicts within two environmentally significant investment landscapes, the Oban-Korup Forest Block, Nigeria, and Lower Baro-Akobo River Basin, Ethiopia. Findings reveal that investments tend to conflict with socially and environmentally valuable land uses, largely as a result of institutional failings. The paper identifies a number of underlying institutional challenges that need to be addressed in order to achieve sustainable development objectives within Africa’s many emerging investment landscapes. Findings have relevance for the development of sustainable landscape governance systems and the alignment of global governance innovations with landscape-level policy arrangements.